(untitled) - Akhiezer, A. I. (New York, 1965)
This classic work presents the main results and calculational procedures of quantum electrodynamics in a simple and straightforward way. Designed for the student of experimental physics who does not intend to take more advanced graduate courses in theoretical physics
Keywords: Quantum electrodynamics,Điện động lực học lượng tử